2019
DOI: 10.1021/acs.joc.8b02891
|View full text |Cite
|
Sign up to set email alerts
|

C–C Bond-Forming and Bond-Breaking Processes from the Reaction of Diesters with Me3SnLi. Synthesis of Complex Bridged Polycycles and Dialkyl Aromatic Compounds

Abstract: 1,2-Aromatic diesters can be transformed into strained bridged polycyclic structures by a two-step procedure consisting of an initial reductive alkylation promoted by alkaline metals, followed by a reaction of the resulting unsaturated diesters with Me3SnLi. We propose that a stanna-Brook rearrangement plays a fundamental role in the formation of the polycyclic organotin acetals obtained. These unusual compounds could be further functionalized by tin–lithium exchange followed by alkylation of the newly formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In 2017, Huang and coworkers found that copper‐catalyzed dehydrogenative formal [3 + 2] cycloadditions of methylnaphthalenes and electron‐deficient alkenes can be used for the construction of 2,3‐dihydro‐1 H ‐cyclopenta[ a ]naphthalenes, which may represent a powerful strategy, although just three examples were given (Scheme 1a) [10] . Shortly after, Paleo, Sardina and coworkers disclosed that dimethyl naphthalene‐1,2‐dicarboxylate could be transformed into 2,3‐dihydro‐1 H ‐cyclopenta[ a ]naphthalene by a two‐step procedure consisting of an initial reductive alkylation of naphthalene diester promoted by alkaline metals, followed by a decarbonilation reaction of the resulting unsaturated diesters with Me 3 SnLi [11] . Alternatively, Lecornué, Thibaudeau and coworkers developed another two‐step process to obtain 2,3‐dihydro‐1 H ‐cyclopenta[ a ]naphthalene by using a Pd‐catalyzed Suzuki−Miyaura coupling reaction and a boron trifluoride etherate‐catalyzed cycloaromatization [12] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Huang and coworkers found that copper‐catalyzed dehydrogenative formal [3 + 2] cycloadditions of methylnaphthalenes and electron‐deficient alkenes can be used for the construction of 2,3‐dihydro‐1 H ‐cyclopenta[ a ]naphthalenes, which may represent a powerful strategy, although just three examples were given (Scheme 1a) [10] . Shortly after, Paleo, Sardina and coworkers disclosed that dimethyl naphthalene‐1,2‐dicarboxylate could be transformed into 2,3‐dihydro‐1 H ‐cyclopenta[ a ]naphthalene by a two‐step procedure consisting of an initial reductive alkylation of naphthalene diester promoted by alkaline metals, followed by a decarbonilation reaction of the resulting unsaturated diesters with Me 3 SnLi [11] . Alternatively, Lecornué, Thibaudeau and coworkers developed another two‐step process to obtain 2,3‐dihydro‐1 H ‐cyclopenta[ a ]naphthalene by using a Pd‐catalyzed Suzuki−Miyaura coupling reaction and a boron trifluoride etherate‐catalyzed cycloaromatization [12] .…”
Section: Figurementioning
confidence: 99%
“…[10] Shortly after, Paleo, Sardina and coworkers disclosed that dimethyl naphthalene-1,2-dicarboxylate could be transformed into 2,3-dihydro-1H-cyclopenta[a]naphthalene by a two-step procedure consisting of an initial reductive alkylation of naphthalene diester promoted by alkaline metals, followed by a decarbonilation reaction of the resulting unsaturated diesters with Me 3 SnLi. [11] Alternatively, Lecornué, Thibaudeau and coworkers developed another two-step process to obtain 2,3-dihydro-1H-cyclopenta[a]naphthalene by using a Pd-catalyzed Suzuki À Miyaura coupling reaction and a boron trifluoride etherate-catalyzed cycloaromatization. [12] Recently, Chandrasekhar and coworkers reported an elegant work to assemble cyclopentane-fused naphthalenes by using the Lewis-acid-catalyzed intramolecular [4 + 2] cycloaddition/aromatization of alkyne-, allene-, and alkene-tethered aryne insertion adducts (Scheme 1b).…”
mentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl 3 ) δ 7.62 (d, J = 8.0 Hz, 1H), 7.42 (d, J = 1.7 Hz, 1H), 7.28 (dd, J = 8.0, 1.7 Hz, 1H), 5.23 (dhept, J = 12.9, 6.5 Hz, 2H), 2.62 (q, J = 7.1 Hz, 1H), 1.36 (dd, J = 6.3, 4.2 Hz, 12H), 1.25 (d, J = 7.2 Hz, 3H), 0.86 (s, 9H); 13 C{ 1 H} NMR (126 MHz, CDCl 3 ) δ 167.7, 166.9, 148.9, 132. 5 General Procedure B for the Reductive Alkylation of Diisopropyl Phthalate (1) with Secondary Halides: Preparation of Kinetic Isomers 3. A −78 °C suspension of small pieces of sodium (245 mg, 10.6 mmol) and naphthalene (150 mg, 1.17 mmol) in THF (4 mL) was treated with a solution of 1 (250 μL, 1.06 mmol) in THF (1 mL) and stirred for 6 h. The resulting solution was transferred via cannula to a −78 °C flask, washed with THF (5 mL), and treated with a solution of the corresponding secondary halide (1.17 mmol) in DMF (1 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2 These alkylations occur regioselectively, with the C−C bond formation taking place at both the α positions of the enolate moieties, resulting in two adjacent quaternary centers being formed in the process. Reductive alkylation with different primary bis-electrophiles was achieved starting from anthracene 4 and naphthalene 5 diesters as well to give a variety of fused and bridged polycycles. Although two possible nucleophilic sites are available in these dianionic species, αor γto each enolate group, exclusive α-alkylation was always observed when primary halides or tosylates were used as electrophiles (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%